1999
DOI: 10.1002/(sici)1097-4644(19990601)73:3<321::aid-jcb4>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular matrix inhibits apoptosis and enhances endothelial cell differentiation by a NF?B-dependent mechanism

Abstract: Hormonal and environmental factors that control the growth, differentiation, and regression of the vasculature are of fundamental importance in tumorigenesis and in the choice of therapeutic strategies. To test the hypothesis that estradiol (E2) and basement membrane proteins would affect the survival of vascular endothelial cells (EC), immortalized human umbilical vein endothelial cells (ECV304) were examined for their response to the chemotherapeutic drugs taxol and etoposide. ECV cell apoptosis was inhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 28 publications
2
3
0
Order By: Relevance
“…These data were similar to those obtained from the platelets prepared from healthy control and diabetic patients (11.9 and 15.6 μmol/4 × 10 7 cells , respectively) [14]. Our previous study using the water-soluble cholesterol also showed the intracellular cholesterol level was increased up to 9.6 μmol/4 × 10 7 cells by free cholesterol loading in MIN6s [14]. This result suggested that the LDLs-loading-induced apoptosis of MIN6s might be cause by the accumulation of intracellular cholesterol that activates the stress signaling and result in apoptosis.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…These data were similar to those obtained from the platelets prepared from healthy control and diabetic patients (11.9 and 15.6 μmol/4 × 10 7 cells , respectively) [14]. Our previous study using the water-soluble cholesterol also showed the intracellular cholesterol level was increased up to 9.6 μmol/4 × 10 7 cells by free cholesterol loading in MIN6s [14]. This result suggested that the LDLs-loading-induced apoptosis of MIN6s might be cause by the accumulation of intracellular cholesterol that activates the stress signaling and result in apoptosis.…”
Section: Resultssupporting
confidence: 86%
“…The LDLs treatment also significantly increased the intracellular cholesterol level up to 10.5 μmol/4 × 10 7 cells , if compared to the 8 μmol/4 × 10 7 cells in control (Figure 4b). These data were similar to those obtained from the platelets prepared from healthy control and diabetic patients (11.9 and 15.6 μmol/4 × 10 7 cells , respectively) [14]. Our previous study using the water-soluble cholesterol also showed the intracellular cholesterol level was increased up to 9.6 μmol/4 × 10 7 cells by free cholesterol loading in MIN6s [14].…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…There are hints that vanadium-containing substances can activate the transcription factor NF-κB [16,23,48]. Beneficial effects of vanadate were found in diabetes, e. g., a blood glucose-lowering effect [1,34].…”
Section: Discussionmentioning
confidence: 99%
“…It can provide structural support to tissues through the formation of a meshwork consisting of protein–protein and protein–proteoglycan interactions ( Yue, 2014 ). Furthermore, ECM components can serve as ligands for receptors and transmit signals involved in cellular processes such as proliferation, migration, apoptosis, and differentiation ( Wang and Passaniti, 1999 ; Hynes, 2009 ; Padhi and Nain, 2020 ). Although the biochemical composition of the ECM is tissue-specific, the main components are collagens, proteoglycans, and glycoproteins ( Murphy and Rudge, 1985 ; Frantz et al, 2010 ; Maeda, 2015 ).…”
Section: Introductionmentioning
confidence: 99%